Differences of Methods of Searching Primary Site of Carcinoma Unknown Primary between Traditional and Standard Guideline (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Trends of searching primary has been changed as etiological backup are changing. PET- CT and other viral molecular markers has been included in most recent protocols for searching primary of carcinoma unknown primary (CUP). Despite of the exhaustive effort with traditional tool many unknown primaries are not known. Patients with CUP without localizing primary, are subjected to radical surgery, wide-field radiation and chemotherapy during treatment.Objectives: To determine the effectiveness of localization of the primary tumor by using conventional technique and to compare the outcome of it to the standard guideline.Methods:This was a prospective study. In conventional search, after thorough clinical examination and diagnostic workup, Panendoscopy with bilateral Tonsillectomy and excision of tongue base mucosa in selective cases is done. Biopsy from nasopharynx, Larynx and hypopharynx is done only when clinically suspected. PET-CT and other viral/molecular markers has been done for recent standard protocol group.Results: In conventional method, Out of 29 patient, 6 primaries found. 5 in tonsil and 1 in base of the tongue base. In standard protocol method, out of 34 cases with PET-CT and viral marker 8 primaries detected, 5 in tonsil and 2 in tongue base and 1 in nasopharynx.Conclusion: Unknown head and neck primaries present a diagnostic challenge that outcome in the search of primary for CUP may be improved by digital examination and appropriate tissue examination in traditional detection protocols.Bangladesh J Otorhinolaryngol; October 2020; 26(2): 142-146